2017
DOI: 10.1111/aje.12448
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment of naked mole‐rat burrows in East Africa

Abstract: Naked mole-rats (Heterocephalus glaber) can be extremely long-lived and are resistant to cancer. Hence, they have been proposed as a model organism for delayed ageing. Adaptation to a constant hypoxic and hypercapnic environment has been suggested as reason for their apparent ability to tolerate oxidative stress. Nevertheless, little is known about the natural habitat to which the species evolved. Naked mole-rat burrow environments were assessed in Ethiopia and Kenya. Despite reported thermolability of naked m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 61 publications
2
77
0
1
Order By: Relevance
“…and T.B.H.) and their coworkers recently reported normal [O 2 ] in natural NMR burrows in Africa (52).…”
Section: Discussionmentioning
confidence: 94%
“…and T.B.H.) and their coworkers recently reported normal [O 2 ] in natural NMR burrows in Africa (52).…”
Section: Discussionmentioning
confidence: 94%
“…In social species where numerous animals live within the confined space of the nest, and there is poor gas diffusion through the surrounding soils, the conditions faced (intermittent acute (or chronic) hypoxic and hypercarbic conditions) can be severe. However, reports of the composition of gases, and thus the severity of hypoxia and hypercarbia, in burrows of fossorial species vary greatly, from 20 to 6 kPa O 2 and 1 to 9.5 kPa CO 2 . The timing and location of burrow measurements presumably contribute to this variability, as well as other factors, such as burrow structure, soil type, number of occupants and degree of fossoriality …”
Section: Introductionmentioning
confidence: 99%
“…However, reports of the composition of gases, and thus the severity of hypoxia and hypercarbia, in burrows of fossorial species vary greatly, from 20 to 6 kPa O 2 and 1 to 9.5 kPa CO 2 . 1,[4][5][6][7][8][9] The timing and location of burrow measurements presumably contribute to this variability, as well as other factors, such as burrow structure, soil type, number of occupants and degree of fossoriality. 1,10 The response to hypoxia in mammals may consist of increases in ventilation (to match O 2 supply to metabolic demand; the hypoxia ventilatory response), decreases in metabolic rate (to match metabolic demand to O 2 supply; the hypoxic metabolic response) or a combination of the two.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the brain, naked mole-rats appear to have smaller acid-induced currents and decreased acidinduced cell death, suggesting a further protective mechanism (Husson and Smith 2018). It was recently reported that carbon dioxide levels are elevated in naked mole-rat burrows (Holtze et al 2018), but that the level reached is less than that generally associated with hypercapnia-induced changes in respiration rate. However, the levels of carbon dioxide reached in sleeping chambers where the majority of the colony sleep together remain to be measured.…”
Section: What Selective Pressures Have Driven Evolution Of Pain Insenmentioning
confidence: 99%